2014
DOI: 10.2147/btt.s59574
|View full text |Cite
|
Sign up to set email alerts
|

Anti-TNF therapy in Jordan: a focus on severe infections and tuberculosis

Abstract: BackgroundA high rate of infection has been reported in patients receiving treatment with anti-tumor necrosis factor (anti-TNF). This study describes the rate of and risk factors for serious infections in patients receiving anti-TNF agents in Jordan.MethodsThis retrospective observational study was conducted at a large tertiary referral center in the north of Jordan. Between January 2006 and January 2012, 199 patients who received an anti-TNF agent (infliximab, adalimumab, or etanercept) were included. Patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…During TNFi treatment, TB in RA patients is often disseminated or extra-pulmonary [7, 8, 20], but clinical manifestations of TB during treatment with synthetic DMARDs (sDMARDs) or in rheumatic disease (RD) patients without specific medication remain poorly documented.…”
Section: Introductionmentioning
confidence: 99%
“…During TNFi treatment, TB in RA patients is often disseminated or extra-pulmonary [7, 8, 20], but clinical manifestations of TB during treatment with synthetic DMARDs (sDMARDs) or in rheumatic disease (RD) patients without specific medication remain poorly documented.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the immunological role of TNF-α, the infection caused by anti-TNF-α treatment of the greatest concern is TB; the risk of TB in patients with RA receiving anti-TNF-α treatment has been documented to range from 0.2 to 4% (6). Previous reports estimated extrapulmonary TB to constitute more than 50% of cases of TB in patients treated with anti-TNF-α drugs (4,7,8). In the patients treated with ADA, Dixon et al previously reported that disseminated disease was the most common (40%), although lymph node disease was relatively low (10%) (7).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, in a large cohort of patients with IMIDs, TNF‐α antagonist treatment was not associated with an increased risk of hospitalizations for serious infections, compared with non‐biologic treatment [Grijalva et al, ]. Exposure to more than one anti‐TNF agent during therapy may also be related with a twofold risk of developing a serious infection [Alawneh et al, ].…”
Section: Methodsmentioning
confidence: 99%
“…Extrapulmonary TB was constituted more than 50% of cases of TB in this setting [Keane et al, ; Dixon et al, ; Jauregui‐Amezaga et al, ]. Moreover, extrapulmonary TB has been reported in patients receiving anti‐TNF therapy despite negative screening with a tuberculin skin test (TST) [Alawneh et al, ]. The introduction of latent TB infection screening prior to initiation of therapy precipitated a reduction of the incidence of TB, bringing it close to the levels of the background population [Carmona et al, ].…”
Section: Methodsmentioning
confidence: 99%